TRANSLATION AND VALIDATION OF THE BRAZILIAN VERSION OF THE "QUALITY OF LIFE ASSESSMENT IN SPINA BIFIDA" QUESTIONNAIRE FOR CHILDREN AND TEENAGERS - Jorge Pompermaier; Maria Cristina de Andrade; Marcela Leal da Cruz; Antonio Macedo Júnior
ABSTRACT Objective: To assess the reliability and validity of the Quality of Life Assessment in Spina Bifida (QUALAS), children and teenager's versions (QUALAS C and T, respectively). This is the first self-applicable quality of life assessment tool for patients under 13 years of age, which also addresses the issue of urinary and fecal incontinence. Methods: Two urologists performed the translation of both QUALAS versions. A commission produced a consensus version (Version 2), which was applied as a pilot study to define Version 3. It was then backtranslated into English and compared with the original version for equivalence of concepts. Internal consistency with Cronbach's alpha and the intraclass correlation coefficient (ICC) reproducibility was analyzed after two assessments with an interval from two to four weeks. Convergent and divergent validities between the QUALAS and a generic health-related quality of life questionnaire, the KIDSCREEN-27, were studied through Pearson's correlation. Results: The reliability analysis showed good internal consistency for QUALAS-C (α=0.73) and QUALAS-T (α=0.79) and good reproducibility in both questionnaires (QUALAS-C - ICC=0.86; QUALAS-T - ICC=0.92). For QUALAS-C convergent validity, there was a low correlation between its items (r=0.35). In addition, a low correlation was also found in the divergent validity analysis, when compared to the KIDSCREEN-27 (r≤0.33). Convergent and divergent validities of the QUALAS-T questionnaire had similar results: r=0.46 and r≤0.49, respectively. Conclusions: After the adaptation and validation process, QUALAS-C and QUALAS-T questionnaires showed to be reliable and valid instruments for measuring the health-related quality of life of children and teenagers with spina bifida aged 8 years or older.